Penggunaan Model Pembelajaran Project Based Learning melalui Google Classroom dalam Pembelajaran Menulis Teks Prosedur - Dariyo Soleh (Ideguru: Jurnal Karya Ilmiah Guru, 2021)
Distance Learning Activities (DLA) is a big challenge for teachers because they have never experienced it before. Project Based Learning Model Through Google Classroom is one of the alternatives that can be applied by teachers to Distance Learning Activities (DLA). The purpose of this study is to find out if the Project Based Learning Model through Google Classroom can be applied in learning activities in Grade IXF of SMP Negeri 2 Mirit Kebumen. The Syntax of Project Based Learning is first, fundamental questions, second, designing product planning, third, drawing up a manufacturing schedule, fourth, monitoring the activeness and development of the project, fifth, testing the results, and sixth, evaluation of the learning experience. The results showed that in general, students can make procedure text correctly. The outcome of students learning can be described that the average score is 81, the top score is 94 and the lowest score is 72. There was one student who got 94, three students got 88, seven students got 86, two students got 84, six students got 82, three students got 78, two students got 76, and there were seven students who got 72.